1999
DOI: 10.1590/s0104-79301999000100003
|View full text |Cite
|
Sign up to set email alerts
|

Tc 99m - SCORPION VENOM: LABELLING, BIODISTRIBUTION AND SCINTIIMAGING

Abstract: Labelling of scorpion (Mesobuthus tamulus concanesis Pocock) venom was successfully achieved with Tc 99m using direct tin reduction procedure. Biodistribution studies were carried out in Wistar rats at different time intervals after i.v. administration of the labelled venom. Scintiimages were obtained after scorpion envenoming using a large field of view gamma camera to ascertain the pharmacological action of venom in the body. Within 5 min of administration, labelled venom was found in the blood (27.7%), musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The mixtures were incubated for 20 minutes at room temperature under vacuum conditions. After this period, 1 mL of saline solution was added to reaction vials (0.5 mL in each vial) in order to interrupt the labeling reaction (16,17). The scheme of direct labeling with 99m Tc is displayed in Figure1.…”
Section: Labeling With 99m Tcmentioning
confidence: 99%
“…The mixtures were incubated for 20 minutes at room temperature under vacuum conditions. After this period, 1 mL of saline solution was added to reaction vials (0.5 mL in each vial) in order to interrupt the labeling reaction (16,17). The scheme of direct labeling with 99m Tc is displayed in Figure1.…”
Section: Labeling With 99m Tcmentioning
confidence: 99%
“…Venom levels were maximal at 30 minutes after administration; after two hours of experiment these concentrations plummeted, and no venom could be detected in any tissue at eight hours after envenomation. Radioactivity tracer experiments using technetium-99 showed that Mesobuthus tamulus venom could be detected in the lungs of rats at five minutes after envenomation (35). Such a rapid distribution of the venom in the lungs, together with intense pulmonary hemorrhage, support the hypothesis that the venom has a direct action on organs and ultimately leads to development of pulmonary edema and impairment of the cardiac function, as observed in classical scorpion envenomation syndrome.…”
Section: Resultsmentioning
confidence: 72%
“…In fact, in experimental animals the level of venom in blood declines as much as 6 fold within 1 hour after administrating venom [26]. During this time, the venom is redistributed to other tissues [26].…”
Section: Discussionmentioning
confidence: 99%
“…During this time, the venom is redistributed to other tissues [26]. Kidney tissue accumulates the largest concentration of venom after this redistribution, and because this is coupled with a slow removal rate of venom, the exposure of renal tissue to venom may be of a duration as prolonged as in the experiments described in this report [2628].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation